Effect of olive oil in dairy cow diets on the fatty acid profile and sensory characteristics of cheese - Vargas-Bello-Pérez, E.; Geldsetzer-Mendoza, C.; Morales, S.M.; Toro-Mujica, P.; Fellenberg, M.A.; Ibáñez, R.A.; Gómez-Cortés, P.; Garnsworthy, P.C. (2018)
The effect of dietary unrefined olive oil (OO) residues and hydrogenated vegetable oil (HVO) on the fatty acid profiles of milk and cheese and the sensory characteristics of cheeses was determined. For 9 weeks, animals were fed a control diet with no added lipid (n = 5 cows), or fat-supplemented diets containing OO or HVO (in both cases n = 5 cows; 30 g kg-1 dry matter). Compared with control and HVO, OO increased C18:1 cis-9, and C18:3 cis-9, cis-12, cis-15 fatty acids in milk; and also increased C18:1 trans-10, C18:1 trans-11, C18:1 cis-9, C18:2 cis-9, trans-11 and C18:3 cis-9, cis-12, cis-15 fatty acids in cheeses. OO reduced the number of holes, overall odour and acidity of cheeses, whereas HVO increased the cow milk odour, bitterness and acidity of cheeses. Overall, OO can improve the cheese fatty acid profile, but with adverse effects on sensory attributes.